A living desert - Spencer, Guy J. (Mahwah, N.J. : Troll Associates, 1988)
Describes the plants and animals of the Sonoran Desert of the American Southwest.
Keywords: Desert biology -- Sonoran Desert -- Juvenile literature; Deserts -- Arizona -- Juvenile literature; Deserts -- Southwest, New; Desert animals; Desert plants; Sonoran Desert